2022
DOI: 10.3390/foods11223641
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature Changes on the Rice Starch Structure and Digestive Characteristics: One and Two-Step Annealing

Abstract: This study investigated the effects of annealing on the structural and physicochemical properties of rice starch below the onset temperature (To) by 5 °C and 15 °C. The results revealed that annealing improved the gelatinization temperature of rice starch, decreased the swelling power, solubility, and paste viscosity of rice starch, and had no significant effects on the morphological structure and crystal configuration of rice starch. In one-step annealing, the annealing temperature of 60 °C is more conducive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…The strong interactions between amylose and amylopectin molecules prevented their leaching from the granules [16,21,22]. The results reported by Xiang et al confirmed the results reported by Dutta et al and Shi et al [13,20,23]. They pointed out that the ANN-based modification of starch, realized at the hydrothermal treatment temperature, promoted the rearrangement of starch molecular chains, resulting in the formation of a perfect crystal structure.…”
Section: Thermal Treatment 211 Hydrothermal Treatmentsupporting
confidence: 73%
See 1 more Smart Citation
“…The strong interactions between amylose and amylopectin molecules prevented their leaching from the granules [16,21,22]. The results reported by Xiang et al confirmed the results reported by Dutta et al and Shi et al [13,20,23]. They pointed out that the ANN-based modification of starch, realized at the hydrothermal treatment temperature, promoted the rearrangement of starch molecular chains, resulting in the formation of a perfect crystal structure.…”
Section: Thermal Treatment 211 Hydrothermal Treatmentsupporting
confidence: 73%
“…The results reported by Ma et [13,20,22,23]. They reported that the swelling power, solubility, leached amylose content, viscosity, and ∆H (enthalpy change) of starch subjected to conditions of hot steam treatment were lower than those of natural starch.…”
Section: Thermal Treatment 211 Hydrothermal Treatmentmentioning
confidence: 94%
“…The internal rearrangement as well as the formation of a more ordered structure led to crystalline perfection [32]. Under the same total tempering time of 96 h, it was found that less cycled annealing treatment contributed to a more stable structure, which was similar to the two-stage annealing of rice starch [33] and starch from Castanopsis sclerophylla under annealing conditions for one-and two-step annealing [34]. After multi-stage annealing, starch was less conducive to the transformation from an imperfect to a perfect crystalline structure, thereby inhibiting the formation of new microcrystalline structures.…”
Section: Crystalline Propertiesmentioning
confidence: 78%
“…Based on the in vitro digestibility determined through the hydrolysis of starch by a mixture of α-amylase and amyloglucosidase, starch can be classified into rapid digestible starch (RDS, completely digested within 20 min), slowly digestible starch (SDS, digested between 20 and 120 min), very-slowly digestible starch (Very-SDS, digested between 120 min and 16 h), and resistant starch (RS, not fully digested in 16 h) [20]. Though much previous literature has demonstrated the effects of ANN on resistant starch content, the outcome actually depends on the starch source and annealing conditions [14,[17][18][19][20]24,27,33,38]. Table 5 showed the effect of continuous and cycled ANN treatments on the in vitro digestibility of water caltrop starch.…”
Section: In-vitro Digestibilitymentioning
confidence: 99%
“…Da mesma forma, [ 9 ] relataram que os valores de TPC de amido de arroz vermelho e integral também foram impactados quando modificados com annealing. Segundo [ 37 ] a temperatura de recozimento e o tempo de tratamento térmico afeta a termoestabilidade de compostos bioativos. Além disso, acreditamos que as ligações de hidrogênio intermoleculares formadas entre amido nativo e TPC influenciaram na sua degradação, quando submetido ao annealing.…”
Section: Resultsunclassified